Analisis Pengetahuan Dan Dukungan Keluarga Dengan Pemberian Imunisasi Dasar Di Wilayah Kerja Puskesmas Parsoburan Kecamatan Siantar Marihat Kota Pematang Siantar Tahun 2023 - Nintaida Gultom; Martaulina Sinaga; Petra Diansari Zega; Adelina Sembiring; Lisbet Gurning; Dina Afriani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Immunization is one of the main goals of vaccination, which is basically can have passive or active immunity. Immunization is carried out in order to prevent the occurrence of diseases that can be prevented by carrying out immunization. The government is obliged to provide complete immunization for every baby and child. This study aims to analyze family knowledge and support for the completeness of basic immunization in the working area of the Parsoburan Health Center. This type of research is a quantitative study using a cross sectional approach. The number of samples in this study were 40 research samples. After conducting the research, it can be concluded that there is a relationship between knowledge and the infant's immunization status, a p-value of 0.000 is obtained, which is less than 0.05. There is a relationship between family support and infant immunization status with a p-value = 0.000 where the value is less than 0.05. It is hoped that the puskesmas will always provide information related to basic immunization for infants.